MOTIF INDIVIDU TERGABUNG DALAM KOMUNITAS MOTOR VESPA DI DENPASAR - Putra, Hafizh Naufal; Arjawa, I Gst Putu Bagus Suka; Kamajaya, Gede; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research aims to find out the problem based on how individual motives in the community. Communities are seen as interactions in social structures that reside in different locations and may be united by the same interests or values, such as automotive enthusiast communities and so on. The problem summary in this research is to find out the motives and benefits of individuals joining Vespa community in Denpasar and what factors motivate individuals to join the community and what benefits the individuals feel.The results known that members of the Vespa community have motives to fulfill their respective interests and needs. Such as the motive for achievement, the motive for self-development, the motive for relationships or friendship and the motive for power. With different motives with the same goal, namely meeting their respective needs. The power motive, wanting to gain respect or promote oneself.